Relationship Between Investment Popularity and Accounting Information: Evidence from the UK Equity Crowdfunding Market - Patel, Jaimin (2016)
This study looks at the use of accounting disclosure in equity crowdfunding to understand how accounting and financial reporting facilitates start-up financing. Results find no relation between historical accounting disclosure and start-up capital obtained from crowdfunding investors, on average. However, results show that there is a relationship between firms set campaign characteristics, such as equity offered and the threshold of voting rights, and campaign success. This study also examines investors’ demand for the financial health of crowdfunding campaigns that disclose financial statements, through the use of traditional accounting ratios, and finds that investors may not take in to consideration the current financial standings of the companies they choose to invest in. Finally, this study finds a negative relation between the number of investors a campaign attracts and the entrepreneur’s long-term forecasts of expected future profits. The results provide insight into the demand for financial reporting in an unregulated market, and informs the debate on proposed crowdfunding regulation.